Differential analysis of ubiquitin-proteomics in skeletal muscle of Duroc pigs and Tibetan fragrant pigs - Li, Meng-yu; Li, Chao-cheng; Chen, Xin; Yao, Yi-long; Han, Yu-song; Guo, Tao; Zhang, Yong-sheng; Huang, Tao (Frontiers in Veterinary Science, 2024)
Understanding the differences in ubiquitination-modified proteins between Duroc pigs and Tibetan fragrant pigs is crucial for comprehending the growth and development of their skeletal muscles. In this study, skeletal muscle samples from 30-day-old Duroc pigs and Tibetan fragrant pigs were collected. Using ubiquitination 4D-Label free quantitative proteomics, we analyzed and identified ubiquitination-modified peptides, screening out 109 differentially expressed ubiquitination-modified peptides. Further enrichment analysis was conducted on the proteins associated with these differential peptides. GO analysis results indicated that the differential genes were primarily enriched in processes such as regulation of protein transport, motor activity, myosin complex, and actin cytoskeleton. KEGG pathway analysis revealed significant enrichment in pathways such as Glycolysis/Gluconeogenesis and Hippo signaling pathway. The differentially expressed key ubiquitinated proteins, including MYL1, MYH3, TNNC2, TNNI1, MYLPF, MYH1, MYH7, TNNT2, TTN, and TNNC1, were further identified. Our analysis demonstrates that these genes play significant roles in skeletal muscle protein synthesis and degradation, providing new insights into the molecular mechanisms of muscle development in Duroc pigs and Tibetan fragrant pigs, and offering theoretical support for breeding improvements in the swine industry.